Pull Factors of Student Migration for Studying Abroad: A Sociological Analysis - Adhikari, Shukra Raj; Thapa, Ambika (The Himalayan Geographers, 2024)
Migration is a process of social transformation. It has become universal phenomenon in the contemporary society. Educational migration is rapidly increase in the world This research aims to analyze pulling factors of student migration for abroad studying from Nepal. Case study method has been applied to collect the primary data. fifteen cases were selected under the procedure of purposive sampling method. A content analysis method has been applied to analyze the collected both primary and secondary data. The students are pulling to the core country for study due to flexible study options and job prospects, numerous education choices, earning and studying at the same time leading to an economically independent life, and simplified residency opportunities at the core country. Further, the social media which has highlighted the living standard of such a country lures the people from the peripheral regions and has stimulated the earning to provide such life for themselves and their family. These facts have been analog to the theoretical concept of the world system which was explained by Wallenstein.